2022
DOI: 10.1111/aor.14251
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced proliferation and differentiation of human mesenchymal stem cells in the gravity‐controlled environment

Abstract: Background Human bone marrow mesenchymal stem cells (hMSCs) present a promising cell source with the potential to be used for curing various intractable diseases, and it is expected that the development of regenerative medicine employing cell‐based therapy would be significantly accelerated when such methods are established. For that, powerful methods for selective growth and differentiation of hMSCs should be developed. Methods We developed an efficient method for hMSC proliferation and differentiation into o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Most of the research was thus for only conducted in a simulated MG (SMG) environment produced by a clinostat or rotating vessel, since examining the proliferation and differentiation patterns of MSCs in an actual MG environment led to some technical and budgetary challenges[ 44 ]. Quynh et al [ 45 ] found that SMG inhibited the proliferation of human umbilical cord MSCs by blocking the cell cycle; in contrast, a study by Nakaji-Hirabayashi et al [ 46 ] revealed a proliferative effect. The various SMG action times could be responsible for this circumstance.…”
Section: Physical Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the research was thus for only conducted in a simulated MG (SMG) environment produced by a clinostat or rotating vessel, since examining the proliferation and differentiation patterns of MSCs in an actual MG environment led to some technical and budgetary challenges[ 44 ]. Quynh et al [ 45 ] found that SMG inhibited the proliferation of human umbilical cord MSCs by blocking the cell cycle; in contrast, a study by Nakaji-Hirabayashi et al [ 46 ] revealed a proliferative effect. The various SMG action times could be responsible for this circumstance.…”
Section: Physical Stimulimentioning
confidence: 99%
“…Shorter SMG treatments appeared to inhibit osteogenesis[ 47 - 49 ] and promote endothelial cell differentiation[ 48 ], neuronal differentiation[ 44 , 48 ], and adipogenic differentiation[ 48 , 49 ]. However, extended SMG decreased the potential for chondrogenic differentiation in MSCs[ 50 ] and encouraged their differentiation toward osteogenesis[ 46 , 48 ]. Different SMG action times had different effects on the cytoskeleton and could even lead to the aforementioned changes through different signal transduction pathways.…”
Section: Physical Stimulimentioning
confidence: 99%
“…The cell differentiation process seems to be the key event affected in space expeditions, as suggested by analyzing specific cell cultures of cartilage, bone and muscle postexploration or induced gravitational variations [ 54 , 55 , 56 ]. Kacena and colleagues performed in vitro hypergravity experiments and presented altered actin and fibronectin elements, modifying the osteoblast–substrate adhesion [ 57 ].…”
Section: Mesenchyme-derived Tissue Formation Adaptability In Space-li...mentioning
confidence: 99%
“…24 Exposure to ethylene oxide (EO) gas and gamma (γ) irradiation are two sterilization methods, which apply their sterilizing effects by changing the biomolecules of the residing microorganisms by chemical modifications or energy forces, respectively. 25 However, they may also alter the structural, mechanical, and biological features of the ECM by transforming proteins or other biological molecules. 26 Such effects have been studied in collagen-based reconstituted scaffolds, 27,28 human, [29][30][31] and porcine ADMs, 32 whereas the effects of the sterilization method on the properties of the bovine ADM have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Scaffolds derived from ECMs need to be terminally sterilized as they pass through several decellularization and processing steps which are not conducted under sterile conditions 24 . Exposure to ethylene oxide (EO) gas and gamma (γ) irradiation are two sterilization methods, which apply their sterilizing effects by changing the biomolecules of the residing microorganisms by chemical modifications or energy forces, respectively 25 . However, they may also alter the structural, mechanical, and biological features of the ECM by transforming proteins or other biological molecules 26 .…”
Section: Introductionmentioning
confidence: 99%